Faktor-faktor berisiko yang menyumbang kepada tingkah laku devian : Satu kajian ulasan sistematik - Tharshini, N. K.; Fauziah, Ibrahim (Universiti Pendidikan Sultan Idris (UPSI), 2020)
This article is prepared to review risk factors which contribute towards deviant behavior. A systematic review was conducted to obtain information regarding the factors that influence risk behavior in databases such as Emerald, Elsevier, Sage and Google Scholar. The result indicates that there are five main factors which contribute towards deviant behavior namely; (i) individual factor, (ii) family factor, (iii) friends factor, (iv)school factor, and (v) community factor. The finding also stipulates that risk factors enhance the potential of an individual to get involved in criminal activities as well as contributes towards intensifying the recidivism rate. The findings of the study implicates the concerned parties regarding the domains that contribute towards deviant behavior so that a preventive measure can be initiated to control the escalation of social phenomena.